Greenland Ice Sheet Surfaces Colonized by Microbial Communities Emit Volatile Organic Compounds - Doting, Eva L.; Davie-Martin, Cleo L.; Johansen, Anders; Benning, Liane G.; Tranter, Martyn; Rinnan, Riikka; Anesio, Alexandre M. (Frontiers in Microbiology, 2022)
Volatile organic compounds (VOCs) are emitted by organisms for a range of physiological and ecological reasons. They play important roles in biosphere-atmosphere interactions and contribute to the formation of atmospheric secondary aerosols. The Greenland Ice Sheet is home to a variety of microbial communities, including highly abundant glacier ice algae, yet nothing is known about the VOCs emitted by glacial communities. We present, for the first time, VOC emissions from supraglacial habitats colonized by active microbial communities on the Southern Greenland Ice Sheet during July 2020. VOC emissions of C5-C30 compounds from bare ice, cryoconite holes, and red snow were collected using a push-pull chamber active sampling system. A total of 92 compounds were detected, yielding mean total VOC emission rates of 3.97  0.70 g m-2 h-1 from bare ice surfaces (n = 31), 1.63  0.13 g m-2 h-1 from cryoconite holes (n = 4), and 0.92  0.08 g m-2 h-1 from red snow (n = 2). No correlations were found between VOC emissions and ice surface algal counts, but a weak positive correlation (r = 0.43, p = 0.015, n = 31) between VOC emission rates from bare ice surfaces and incoming shortwave radiation was found. We propose that this may be due to the stress that high solar irradiance causes in bare ice microbial communities. Acetophenone, benzaldehyde, and phenylmaleic anhydride, all of which have reported antifungal activity, accounted for 51.1  11.7 % of emissions from bare ice surfaces, indicating a potential defence strategy against fungal infections. Greenland Ice Sheet microbial habitats are, hence, potential sources of VOCs that may play a role in supraglacial microbial interactions, as well as local atmospheric chemistry, and merit future research efforts.